Principal's Leadership Strategy in Enhancing the Quality of Teacher Human Resources at Pengantigan Public Elementary School, Banyuwangi Regency - Fernanda, Alvina Arti; Wilujeng, Sri; Wahyudiono, Andhika (PT. LITERASI SAINS NUSANTARA, 2024)
The lack of enthusiasm at this school poses a significant challenge that impedes its progress. Prospective parents may hesitate to enroll their children in schools with minimal interest, preferring those with a vibrant atmosphere. This study aims to examine the Principal's Leadership Strategy for Enhancing the Quality of Teacher Human Resources at Pengantigan Elementary School. Specifically, it seeks to understand how the principal's leadership strategies enhance teacher quality at Pengantigan Elementary School in Banyuwangi Regency, and to identify challenges encountered in implementing these strategies. This qualitative research employed descriptive methods, including interviews, observations, and document analysis. Findings reveal that the principal of Pengantigan Public Elementary School adopts a transformational leadership approach consistent with Jems MacGregor Burns' leadership theory. Key strategies include: (1) Articulating a clear and inspiring vision, (2) Motivating and empowering teachers, (3) Stimulating intellectual growth, (4) Exemplifying charisma and leading by example, and (5) Considering individual needs. In conclusion, the effectiveness of teacher development at SDN Pengantigan hinges on the principal's adeptness in guiding and motivating teachers with appropriate strategies.